Characterization of Waste Material Derived Willemite-Based Glass-Ceramics Doped with Erbium - G. V. Sarrigani; H. J. Quah; W. F. Lim; K. A. Matori; N. S. Mohd Razali; A. Kharazmi; M. Hashim; H. R. Bahari (Advances in Materials Science and Engineering)
We reported, for the first time, to the best of our knowledge, the production of erbium doped willemite-based glass-ceramic using waste material. In this work, a willemite-based glass-ceramic was prepared from waste material to obtain excellent crystallinity and then doped with trivalent erbium (Er3+) to yield ([(ZnO)0.5(SLS)0.5]1−x[Er2O3]x) final composition where x=3 wt%. The samples were sintered at various temperatures (500–1100°C) to study the effects of sintering temperatures on microstructure and physical properties of the samples. X-ray diffraction (XRD) and Fourier transform infrared (FTIR) were used to determine structural changes and functional groups in the samples, respectively. Field-emission scanning electron microscopy (FE-SEM) equipped with energy dispersive X-ray was used to observe surface morphology and to detect presence of elements in the samples. Findings showed that average grain size of the Er3+ doped glass-ceramic sample increased as a function of the sintering temperature and the optimum temperature was 900°C.